Clinical outcomes following identification of an incidental p53 signature in the fallopian tube - Emily C. MacARTHUR; Mackenzy RADOLEC; T. Rinda SOONG; Esther ELISHAEV; Ronald BUCKANOVICH; Sarah E. TAYLOR; Jamie LESNOCK (Gynecologic Oncology Reports, 2024)
Fallopian tube pathology in patients with BRCA1 and BRCA2 mutations suggests a possible pathway to high grade serous ovarian carcinoma originates with a p53 signature, which is thought to represent a potential precursor to serous tubal intraepithelial carcinoma (STIC). The clinical implications of an isolated p53 signature in the average-risk population has not been well-established. This study aims to describe clinical outcomes in patients with incidentally noted p53 signature lesions.All patients diagnosed with a p53 signature lesion on final pathology from 2014 to 2022 were identified at a large academic institution. P53 signature is defined by our lab as morphologically normal to mildly atypical tubal epithelium with focal p53 over-expression on immunohistochemistry. Incidental p53 signature was defined as identification of a fallopian tube lesion excised for benign or unrelated indications in patients without a known hereditary disposition. Demographic, clinicopathologic, and genetic data were collected.A total of 127 patients with p53 signatures were identified. Thirty-six patients were excluded for established ovarian cancer or high-risk history leaving 91 total patients. Five patients (5.5%) developed a malignancy, none of which were ovarian or primary peritoneal, at the end of the eight and a half year follow up period. Twenty-four (26.4%) patients had salpingectomy without any form of oophorectomy at the time of initial surgery, while 67 (73.6%) patients had at least a unilateral oophorectomy at the time of their salpingectomy. Seven patients (7.7%) had additional surgery after p53 signature diagnosis; however, the final pathology yielded no evidence of malignancy in all these patients. After subsequent surgeries, 19 (20.9%) patients maintained their ovaries. The diagnosis of an incidental p53 signature was not associated with any primary peritoneal or ovarian cancer diagnoses during our follow up, and the majority of patients were managed conservatively by their providers with no further intervention after diagnosis.